Desarrollo de una herramienta tipo Business To Consumer para la venta electrónica de productos y servicios del Área Energía , las Industrias y los Recursos Naturales no Renovables de la Universidad Nacional de Loja. - Paucar Córdova, Rosman José (2011)
The present investigation work takes like topic: I "develop of a tool type Business to Consumer for the electronic sale of Products and Services of the Area of The Energy, The Industries and The Natural Resources not Renewable of the National University of Loja", and their main objective is the diffusion and electronic commercialization of the products and services with which they are Not counted in the Area of The Energy, The Industries and The Natural Resources Renewable of the National University of Loja to the collective in general by means of a system computer type B2C, together with the creation of a digital collection of products and services that besides not having problems of readiness, they look for to take advantage of the internal production of the same ones. This tool allows to consent so much to students of our university like those of other universities, public and private institutions and collective in general to a without number of investigative works, projects, thesis, services of computation laboratories, shops electric and more services with which the Area counts, what allows him/her to be visited by people that are inside and outside of our city Finally it is very important to highlight that this application is properly documented with programmer's manuals and of user for a better understanding, as much in form as in design.